Pengaruh Laba Rugi Perusahaan, Prediksi Kebangkrutan, dan Jenis Industri Terhadap Audit Delay pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia - Eva Anggra Yunita; Mohammad Arridho Nur Amin (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Publication of financial reports by companies going public is an obligation. Even though the provisions for submitting the maximum time for publication of audited financial statements have been determined, many companies are still late in submitting their audited financial reports. Likewise, what happened to issuers belonging to the LQ45 index. This study aims to determine whether or not there is an effect of company profit and loss, bankruptcy prediction and type of industry on audit delay in LQ45 companies. This type of research uses quantitative research, where the data used is in the form of numbers. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange in 2017-2021 with a total of 45 companies. The sampling technique used purposive sampling technique. The data collection method uses secondary data. This study produces a company profit and loss variable and bankruptcy prediction has no effect on audit delay. Meanwhile, the type of industry has an effect on audit delay. Where, if the company is a non-financial industry, the potential for audit delay is higher.